The Clinical Course and Prognosis of Patients With Nontuberculous Mycobacterial Pulmonary Disease After Solid Organ Transplantation - Kim, Joong-Yub; Han, Ahram; Lee, Hajeong; Ha, Jongwon; Lee, Kwang-Woong; Suh, Kyung-Suk; Yi, Nam-Joon; Min, Sangil; Hong, Suk Kyun; Kim, Yong Chul; Choi, YoungRok; Yim, Jae-Joon; et al. (Journal of Korean medical science, 2023)
Due to impaired cell-mediated immunity, solid organ transplantation (SOT) recipients are at increased risk of developing nontuberculous mycobacterial pulmonary disease (NTM-PD). However, the clinical course of NTM-PD in SOT patients and the impact of SOT on the prognosis of NTM-PD remain unclear. We analyzed patients who developed NTM-PD after receiving SOT between January 2001 and December 2020, at a tertiary referral hospital in South Korea. Baseline characteristics, clinical course, and prognosis were evaluated. Propensity score-matched analysis was performed to assess the impact of SOT on long-term survival in patients with NTM-PD. Among 4,685 SOT recipients over 20 years, 12 patients (median age, 64 years; interquartile range [IQR], 59-67 years; men, 66.7%) developed NTM-PD. Seven (58.3%) and five (41.7%) patients underwent kidney and liver transplantation, respectively, before the diagnosis of NTM-PD. The incidence of NTM-PD was 35.6 cases per 100,000 person-years among kidney transplant recipients and 28.7 cases per 100,000 person-years among liver transplant recipients. The median time between transplantation and the diagnosis of NTM-PD was 3.3 (IQR, 1.5-10.8) years. The most common mycobacterial species was (50.0%). Antibiotic treatment was initiated in five (41.7%) patients, and two patients (40.0%) achieved microbiological cure. Two patients died during a median follow-up of 4.2 (IQR, 2.3-8.8) years and NTM-PD was assumed to be the cause of death in one patient. When matched to patients without a history of SOT, patients with a history of SOT did not show worse survival ( value for log-rank test = 0.62). The clinical course of NTM-PD in SOT recipients was comparable to that of patients without SOT, and SOT did not increase the risk of all-cause mortality in patients with NTM-PD.